2021
DOI: 10.1248/bpb.b20-00916
|View full text |Cite
|
Sign up to set email alerts
|

The Optimal Dose of Tacrolimus in Combination Therapy with an Anti-TNFα Antibody in a Mouse Colitis Model

Abstract: An attempt to use combination therapy with anti-tumor necrosis factor α (TNFα) antibodies and tacrolimus (TAC) has been tried to induce remission in ulcerative colitis (UC). However, the optimal dose of TAC in combination therapy with anti-TNFα antibodies (TAC anti-TNFα therapy) remains unclear. We examined the efficacy of various doses of TAC anti-TNFα therapy in a mouse colitis model. Dextran sulfate sodium induced colitis model mice were divided into an anti-TNFα antibody monotherapy group and the groups th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…in the inflamed colon. 32) Accumulated evidences showed that the serum TNF-α level as well as colonic TNF-α concentration were all significantly elevated in acute colitis, [33][34][35][36] and the elevated TNF-α is positively correlated with the severity of UC, 36) indicating the vital role of TNF-α in the pathogenesis of UC. 37) Results from our study showed that the serum TNF-α level was markedly increased in colitis rats, and the increased TNF-α level was positively correlated with elevated TBA and TBil, indicating that the increased TNF-α may contribute to the intrahepatic cholestasis of acute colitis.…”
Section: Discussionmentioning
confidence: 99%
“…in the inflamed colon. 32) Accumulated evidences showed that the serum TNF-α level as well as colonic TNF-α concentration were all significantly elevated in acute colitis, [33][34][35][36] and the elevated TNF-α is positively correlated with the severity of UC, 36) indicating the vital role of TNF-α in the pathogenesis of UC. 37) Results from our study showed that the serum TNF-α level was markedly increased in colitis rats, and the increased TNF-α level was positively correlated with elevated TBA and TBil, indicating that the increased TNF-α may contribute to the intrahepatic cholestasis of acute colitis.…”
Section: Discussionmentioning
confidence: 99%